2017
DOI: 10.1002/asia.201700469
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of [VIVO(acac)2] with Human Serum Transferrin and Albumin

Abstract: [VO(acac) ] is a remarkable vanadium compound and has potential as a therapeutic drug. It is important to clarify how it is transported in blood, but the reports addressing its binding to serum proteins have been contradictory. We use several spectroscopic and mass spectrometric techniques (ESI and MALDI-TOF), small-angle X-ray scattering and size exclusion chromatography (SEC) to characterize solutions containing [VO(acac) ] and either human serum apotransferrin (apoHTF) or albumin (HSA). DFT and modeling pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 140 publications
1
20
3
Order By: Relevance
“…These serum proteins also led to % 6-fold decrease in cellular V content from the treatment of T98g cells with 50 mm 1 for 4 h ( Figure S4). Thus, contrary to literature postulates, [19] V binding to Tf is not required for its cellular uptake and cytotoxicity, as described elsewhere. [21] The higher cytotoxicity of fresh 1 vs. its decomposition products in all cell lines ( Figure 2) correlated with higher cellular V content ( Figure S4).…”
contrasting
confidence: 89%
“…These serum proteins also led to % 6-fold decrease in cellular V content from the treatment of T98g cells with 50 mm 1 for 4 h ( Figure S4). Thus, contrary to literature postulates, [19] V binding to Tf is not required for its cellular uptake and cytotoxicity, as described elsewhere. [21] The higher cytotoxicity of fresh 1 vs. its decomposition products in all cell lines ( Figure 2) correlated with higher cellular V content ( Figure S4).…”
contrasting
confidence: 89%
“…indicates that the neutral compounds penetrate the erythrocyte membrane through passive diffusion, being found in the intracellular medium in amounts higher than 50%. Alternatively, inside the red blood cells, the compounds [V IV O(mal) 2 Finally, studies concerning to the transport of vanadium complexes in blood, concluded that vanadium complexes are mostly transported by transferrin (hTf) [69][70][71][72][73]. At low micromolar concentrations, assuming that V(IV) maintains its oxidation state, most of the complexes hydrolyse and vanadium(IV) is transported as (VO)hTf, with V(IV)O bound at one of the iron sites [69][70][71][72][73].…”
Section: Tablementioning
confidence: 99%
“…It has been reported that V in the form of vanadyl (VO 2+ , tetravalent V 4+ state) binds to Tf at the same binding site as the Fe 3+ ion [97] and that V 5+ , for which the cationic form (dioxovanadium cation, VO2 + ) has been indicated, also occupies the same pockets as Fe 3+ [98]. Studies conducted by Azevedo et al [99] have confirmed that both V 4+ and V 5+ can bind to apo-Tf and holo-Tf, thus they can be efficiently up-taken by cells through receptor-mediated endocytosis of Tf.…”
Section: Vanadium -Metabolism: a Summary Of Key Informationmentioning
confidence: 99%